NILAI RELIGIUSITAS DALAM TINJAUAN SAJAK “POTRET KELUARGA” KARYA WS RENDRA - Gilang Tresna; Maryana Maryana; Nursiti Fatimah; Agus Priyanto (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Literature is a work created by someone who will be published later, so the work he has made can be enjoyed by many people. A literary work written by an author whose purpose to read by others, in a literary work that has been created must have to contain the values that can be taken by readers. Among the many literary works we have read that we find interesting are the poems of "Keluarga Port" by WS Rendra. Poetry is a literary work that reveals the thoughts and feelings of a poet to the problems that exist in himself and his environment. It can also be studied from themes such as romance, religion, and feelings. Knowing that this article will analyze the nilaireligius on the "Portrait of the Family" portrait by WS Rendra. The focus of this article's discussion is the religious aspect that appears in the entire poem by using the critical methodology proposed by Teun A. van Dijk, by paying more attention to aspects of language, discourse, and communication process. This "Family Portrait" poem can give rise to an interpretation that will produce interpretations in understanding the overall religious meaning.